Quantitative Estimation and Validation of Chlorthlidone and Azilsartan Medoximil in Bulk and Tablet Dosage Form by using RP-HPLC - Dighe, Nachiket S.; Thorat, Somnath K.; Shinde, Ganesh S; Dhamak, Kavita V (Journal of Drug Delivery and Therapeutics, 2019)
The first reversed phase high performance liquid chromatographic method for Stability Indicating of, Azilsartan and chlorthalidone has been developed and validated to be a simple, sensitive, rapid, specific, precise, and accurate method. Chromatographic separation was achieved on Zorbax XBD-C8, 250mm × 4.6mm,5µm.Buffer pH5.5 : Methanol (60:40) as a mobile phase at flow rate of 1 ml/min. UV detection was operated at 234 nm and injection volum was 25 μl.. The proposed method showed good linearity, accuracy, precision and was successfully applied for determination of the drugs in laboratory prepared pharmaceutical dosage forms. Keywords: Azilsartan and chlorthalidone, RP-HPLC, Stability Indicating.